ECOLOGICAL AND FAUNA CHARACTERISTIC OF GROUND BEETLES OF DULTYDAG MASSIF - G. M. ABDURAKHMANOV; G. M. BUTAEVA (Юг России: экология, развитие, 2015)
The work is the first in studying ground beetles (Coleoptera, Carabidae) of Dultydag mountain chain; ecological and fauna characteristic is presented, 88 species of 25 genus are revealed. The living forms of the ground beetles are also studied in the work.